Loss a Asessment of Albirzia lebbek Seeds Due to Insect and Fungus Damage - Harsh, N. S. K.; Joshi, K. C. (Indian Forester, 1993)
Damage caused by two insect borers and a fungus to the seeds of Albizia lebbek was quantified. It was observed that by November end almost 50% seeds were damaged whereas by February end this percentage was increased upto 70%. The fungus infected seeds were more in number in Novemeber collections but in seed collections made in February the number of insect damaged seeds was more. The seeds were also noticed to be attacked together by both insect and fungus as well.